Fate of snowmelt in complex subalpine terrain - Webb, Ryan W., author; Gooseff, Michael, advisor; Fassnacht, Steven, committee member; Ramirez, Jorge, committee member; Niemann, Jeffrey, committee member (Colorado State University. Libraries, 2016)
Snow is important to human communities and natural ecosystems around the world that rely on snowmelt runoff for as much as 80% or more of streamflow. In addition to streamflow, snowmelt can drive hydrological processes such as groundwater recharge, soil moisture dynamics, forest ecosystem dynamics, and potentially cause high damage flooding. Multiple environmental controls will cause snow to vary in depth, density, and snow crystal metamorphism causing a complex three dimensional matrix of ice, air, water vapor, and liquid water (during melt) that is non-uniform across a landscape and varies in time at the daily and even hourly scale. Because of the non-uniform dynamics of snow and snowmelt processes, multi-dimensional studies are necessary to determine hydrological flow paths during spring snowmelt. The goal of this dissertation is to investigate the physical processes that control the fate of snowmelt during spring runoff in complex subalpine terrain. These processes were investigated through 1) observing the diurnal pattern of snowmelt in Colorado's Front Range, 2) testing the diversion potential of hydraulic barriers within a layered snowpack through numerical modeling, 3) collecting field data to investigate the spatio-temporal patterns of water distribution during spring snowmelt, and 4) analyzing a network of soil moisture sensors in California's Southern Sierra Nevada to determine the variability of infiltration in a headwater catchment. Observations of the diurnal temporal pattern of snowmelt resulted in a relatively simple method to capture the outflow from a snowpack using hourly snow water equivalent data. The resulting temporal pattern is comparable to design rainfall distribution types specifically for snowmelt that can be important for flood risk analysis or design of channels in previously unmonitored headwater systems. The observed temporal patterns were also used to inform numerical simulations in the modeling package TOUGH2 that utilized additional data from NASA CLPX datasets to simulate meltwater percolation through a melting snowpack. Results of this component of the dissertation displays the potential for hydraulic barriers to form on south, flat, and north aspect hillslopes and potentially divert downward flowing water at similar scales as the topographic or land cover variability. Hydraulic barriers in simulations were permeability barriers only on the south and flat aspect slopes and capillary barriers only on the north aspect slopes. The dynamic nature of a snowpack in the presence of water implies that the capillary barriers are likely short-lived relative to permeability barriers and thus capillary barriers may be important at the day or week timescale and permeability barriers may be more influential at the monthly or seasonal time scale. Field observations near Steamboat Springs, Colorado were made for above normal, relatively normal, and below normal snow seasons including measurements of bulk snow water equivalent and soil moisture on varying slope, aspect, soil parameters, and canopy conditions with results displaying the variability from these influences. Evidence was present of meltwater flowing above the soil surface and through the snowpack. At the base of the north aspect slope the water table rose above the soil surface and the snowpack added storage capacity to the vadose zone. The variability of snowmelt and resulting soil moisture and infiltration dynamics was supported by the analysis of a network of soil moisture sensors in California’s Southern Sierra Nevada. This component of the dissertations displayed the high variability of wetting and drying dynamics beneath a snowpack at the sub-hillslope and watershed scale. Results of this dissertation display that the snowpack acts as an extension of the vadose zone during spring snowmelt and that one-dimensional assumptions are not appropriate in headwater catchments during this time. Consideration of the snowpack and soil together will improve modeling, remote sensing, and water balance calculations for hydrologic studies during spring snowmelt and improvements upon allocation of streamflow, groundwater recharge, and evapotranspiration.
Keywords: groundwater recharge; snow hydrology; soil moisture; hillslope hydrology; flood prediction; snowmelt